The First Report on the Brachyuran Crab Diversity in Mandalika and Their Commercial Value - Murniati, Dewi Citra; Arfianti, Tri (SEAMEO BIOTROP, 2024)
West Nusa Tenggara, Indonesia, encompasses the western part of the Lesser Sunda Islands with a long coastline that supports a rich biodiversity of coastal biota. Brachyuran crabs constitute one of the most diverse invertebrate groups in the coastal ecosystem. This research aimed to record the biodiversity of brachyuran crabs and their commercial value in the Special Economic Zone (SEZ) of Mandalika in Central Lombok, Indonesia. Data were collected by hand, scoop, and trap using the random sampling method. In the current study, we have compiled, for the first time, a checklist of 402 individual brachyuran crabs belonging to 22 genera, 13 families, and 35 species from Mandalika. The present study revealed that Mandalika has a comparable number of species to those in previous studies from other coastal areas on Lombok Island. The commercial value of the crabs is in line with their edibility. The family Ocypodidae comprised 43% of all the brachyuran crabs reported from Mandalika. The findings emphasise the importance of their habitat in Mandalika and the potency of brachyuran crabs to support government food security programs.